OPTIMIZATION OF CARBON NANODOTS PYRROLIC CONJUGATED POLYCLONAL ANTIBODY AS FLUORESCENCE-BASED IMMUNOSENSOR FOR SARS-COV-2 ANTIGEN DETECTION - Rismayanti, Dea
The COVID-19 pandemic, caused by SARS-CoV-2, has posed a significant global challenge with far-reaching public health impacts. While the pandemic has ended, early detection remains necessary to prevent the possibility of a new wave of SARS-CoV-2 or other potential pandemics. To address this challenge, the development of carbon nanodots (CDs)-based biosensors has potential as an efficient and cost-effective solution for early detection of SARSCoV- 2. CDs offer high photostability and good biocompatibility, making them ideal candidates for biosensor construction, one of which is the FRET (Fluorescence Resonance Electron Transfer) immunosensor method. In this study, CDs conjugated with polyclonal antibodies (CDs-Ab) through EDC/NHS coupling were used as donors and graphene oxide (GO) was used as an acceptor to produce the FRET effect in immunosensor system. The treatment of varying concentrations of CDs (0.5; 1; 1.5 mg/mL) and GO (0; 25; 50; 75; 100 ?g/mL), as well as the duration of incubation of CDs-Ab with GO (5-60 minutes), was carried out to obtain the most optimum FRET effect. Then, a sensitivity test was conducted on the immunosensor system using SARS-CoV-2 antigen in the concentration range of 100-5000 ng/mL to test the success of the immunosensor system. The results showed that the most optimum concentration of CDs to be conjugated with antibodies was CDs with a concentration of 1.5 mg/mL, characterized by a consistent emission peak wavelength shift (redshift) at 365 nm excitation. GO concentration of 100 ?g/mL with incubation duration of 5 minutes is the optimum concentration and incubation time to produce FRET effect in the immunosensor system with fluorescence quenching efficiency reaching 45%. The immunosensor system developed was successful in detecting the antigen as indicated by a significant fluorescence value comparison (p-value<0.05) between the antigen variation treatment and the negative control (CDs- Ab+GO). The antigen concentration was found to be linearly related to the fluorescence intensity produced by the immunosensor system (R2 = 0.972) with a detection limit of up to 1.57 ng/mL. These results indicate that pyrrolic carbon nanodots-conjugated polyclonal antibodies can be used as a fluorescence-based immunosensor for SARS-CoV-2 antigen detection.